Visual Aesthetics and the 2021 Burma/Myanmar Spring Revolution - Götz, Johanna M. (Annali di Ca’ Foscari: Serie Orientale)
The 2021 attempted military coup in Burma/Myanmar has uprooted a decade of – partially corrupted – democracy-making. Simultaneously, a creative pro-democratic mobilization has emerged, with calls for alliances that had long been unthinkable. Tracing connections across space and time as symbolically manifested in protest art, this article suggests that insights from the intersectional tradition – in its theoretical conceptualizations and its rootedness in activist praxis – may help to trace the complexity and multiplicity of contemporary mobilization. Moreover, it proposes that an intersectional lens may allow to pay attention to the critical crossroads of imagining a future liberated Burma/Myanmar, beyond the common enemy and towards genuine relational solidarity.